2016
DOI: 10.3389/fphar.2016.00353
|View full text |Cite
|
Sign up to set email alerts
|

FCERI and Histamine Metabolism Gene Variability in Selective Responders to NSAIDS

Abstract: The high-affinity IgE receptor (Fcε RI) is a heterotetramer of three subunits: Fcε RIα, Fcε RIβ, and Fcε RIγ (αβγ2) encoded by three genes designated as FCER1A, FCER1B (MS4A2), and FCER1G, respectively. Recent evidence points to FCERI gene variability as a relevant factor in the risk of developing allergic diseases. Because Fcε RI plays a key role in the events downstream of the triggering factors in immunological response, we hypothesized that FCERI gene variants might be related with the risk of, or with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…On the other hand, several genes were found to be significantly upregulated in T cells from tolerized kidneys, an example being the IgE receptor–related gene Fcer1g ( Supplemental Figure 4B ). This gene has previously been implicated in asthma and allergic reactions ( 36 , 37 ); however, its role in T cell immune tolerance in transplantation remains unknown.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, several genes were found to be significantly upregulated in T cells from tolerized kidneys, an example being the IgE receptor–related gene Fcer1g ( Supplemental Figure 4B ). This gene has previously been implicated in asthma and allergic reactions ( 36 , 37 ); however, its role in T cell immune tolerance in transplantation remains unknown.…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of histamine depends on the expression and activity of histamine receptors [ 36 ]. Histamine metabolism is closely related to food allergy [ 37 ]. Deoxycholic acid and lithocholic acid play a conductive role in maintaining the homeostasis of the bile secretion pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for the selection of the 16 genes included in this study is based on putative mechanisms involved this type of reactions. FCERI plays an essential role in IgE-mediated mechanisms and variants in FCERI genes have been previously described as genetic factors related to asthma (Cui et al, 2003; Kim et al, 2006; Palikhe et al, 2008; Joubert et al, 2011; Ramphul et al, 2014; Yang et al, 2014), allergy (Hasegawa et al, 2003; de Guia et al, 2015; Liao et al, 2015; Amo et al, 2016a,b), and food sensitization (Liu et al, 2011; Hong and Wang, 2012). It has been also described that some variants in genes involved in the vitamin D pathway are related with asthma (Poon et al, 2004; Raby et al, 2004; Wjst, 2005; Wjst et al, 2006; Bossé et al, 2009; Saadi et al, 2009; Li et al, 2011; Pillai et al, 2011; Maalmi et al, 2013; Leung et al, 2015; Hutchinson et al, 2017), especially variations in genes regulated by vitamin D, such as IL4 and its receptor (Burchard et al, 1999; Donfack et al, 2005; Ober and Hoffjan, 2006; Battle et al, 2007; Michel et al, 2010; Baye et al, 2011; Hesselmar et al, 2012; Liu et al, 2012; Micheal et al, 2013; Nie et al, 2013; Zhu et al, 2013; Al-Muhsen et al, 2014; Berenguer et al, 2014; Klaassen et al, 2015; Zhang et al, 2015; Narozna et al, 2016) and IL13 (Black et al, 2009; Bottema et al, 2010; Palikhe et al, 2010; Cui et al, 2012; Accordini et al, 2016; Xu et al, 2017), which are also related to IgE (Marsh et al, 1994; Kabesch et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that the major findings obtained in the present study are novel, since only one of the three SNPs that remained after the multinomial analysis have been previously related with atopy or drug hypersensitivity. Among these, one of the FCER1G SNPs is novel and hence have not been studied before, and the other one has been related with food sensitization (Liu et al, 2011) and has been previously studied in patients with selective hypersensitivity to NSAIDs and allergic rhinitis without significant association (Amo et al, 2016a,b). After the NGS and combined dataset analyses phases, prediction models revealed that one of these SNPs, designated as FCER1G rs36233990 was correct in all models and it allowed an excellent prediction for patients with DHR, IgE-mediated DHR and all IgE-mediated diseases analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation